The Invasion of Microplastics - Machado, C. (Open Schools Journal for Open Science, 2020)
The project consisted of a market study, in order to know the attitudes of the inhabitants of Vila Nova de Famalicão (VNF) towards the use of plastic and to measure the knowledge of the population of VNF about microplastics. Students of various grades that were interested in the theme carried out the project. The main goal was to change mentalities and consequent practices. It was concluded that, although the inhabitants of VNF know what microplastics are and what is at their origin, they do not reveal much concern in changing their daily practices because practical solutions are still not implemented.